Multi-source assisted mixed simultaneous wireless information and power transfer for energy efficient routing in IoT networks - Nagelli, Prasad; Nagavelli, Ramana (Bulletin of Electrical Engineering and Informatics, 2025)
Recently, simultaneous wireless information and power transfer (SWIPT) emerged as the best solution for resource-constrained internet of things (IoT) networks. SWIPT ensures the provision of parallel information and power transfer in the network. Under the SWIPT model, many researchers use two well-established protocols: time switching (TS) and power splitting (PS). TS is better than PS when the signal is weak but inserts an extra delay because energy harvesting (EH) and information decoding (ID) happened two different times. However, PS protocol performs poorly in hard situations with low signal strength even if it conducts EH and ID simultaneously. Hence, this paper proposed a new model called mixed-SWIPT (MSWIPT) which combines TS and PS protocols in an intuitive manner. Further, this work proposes a multi-source EH mechanism in which the receiving node harvests energy from multiple sources which is different from single source, i.e., desired node’s radio frequency (RF) signal. The multiple sources include non-participated Neighbor Node’s RF signal, sink node and co-channel interference and noise. Under the routing, the node selection is formulated as maximum link capacity problems and solved through several constraints. Extensive simulations on proposed model prove the superiority in terms of EH and energy efficiency from the state-of-the-art methods.